Flavonoids as potential wound-healing molecules: emphasis on pathways perspective - Zulkefli, Nabilah; Che Zahari, Che Nur Mazadillina; Sayuti, Nor Hafiza; Kamarudin, Ammar Akram; Saad, Norazalina; Hamezah, Hamizah Shahirah; Bunawan, Hamidun; Baharum, Syarul Nataqain; Mediani, Ahmed; Ahmed, Qamar Uddin; Harun @ Ismail, Ahmad Fahmi; Sarian, Murni Nazira (Multidisciplinary Digital Publishing Institute (MDPI) (Switzerland), 2023)
Wounds are considered to be a serious problem that affects the healthcare sector in many countries, primarily due to diabetes and obesity. Wounds become worse because of unhealthy lifestyles and habits. Wound healing is a complicated physiological process that is essential for restoring the epithelial barrier after an injury. Numerous studies have reported that flavonoids possess wound-healing properties due to their well-acclaimed anti-inflammatory, angiogenesis, re-epithelialization, and antioxidant effects. They have been shown to be able to act on the wound healing process via expression of biomarkers respective to the pathways that mainly include Wnt/βcatenin, Hippo, Transforming Growth Factor-beta (TGF-β), Hedgehog, c-Jun N-Terminal Kinase (JNK), NF-E2-related factor 2/antioxidant responsive element (Nrf2/ARE), Nuclear Factor Kappa B (NF-κB), MAPK/ERK, Ras/Raf/MEK/ERK, phosphatidylinositol 3-kinase (PI3K)/Akt, Nitric oxide (NO) pathways, etc. Hence, we have compiled existing evidence on the manipulation of flavonoids towards achieving skin wound healing, together with current limitations and future perspectives in support of these polyphenolic compounds as safe wound-healing agents, in this review.